The Impact of the Market on Character Formation, Ethical Education, and the Communication of Values in Late Modern Pluralistic Societies - von Hagen, Jürgen; Welker, Michael; Witte, John; Pickard, Stephen (Evangelische Verlagsanstalt, 2020)
Late modern pluralistic societies are characterized by an infinitely multi-coloured individuality of their citizens and a wealth of associations and groups. This »plurality«, which is difficult to grasp, is welcomed by many people as a source of freedom, but feared by others inside and by many observers outside as social chaos. However, this plurality is countered by a limited number of so-called »social systems«, which are to a large extent characterized by organizational, institutional and normative structures and weight. In the theoretical, empirical, and historical contributions to this volume, theologians, economists and market practitioners discuss the many tensions between market economics, ethics and the Christian religion, thus adding to the fruitful and much needed dialogue between economics and theology. With Contributions by Jason Brennan, Michael J. Broyde, Ginny Seung Choi, Samuel Gregg, Peter Lampe, Manfred Lautenschläger, Frank J.